2012
DOI: 10.3390/ijms13055832
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Expression of Glucosinolate Synthesis Genes CYP83A1 and CYP83B1 in Pak Choi (Brassica rapa L. ssp. chinensis var. communis (N. Tsen & S.H. Lee) Hanelt)

Abstract: CYP83A1 and CYP83B1 are two key synthesis genes in the glucosinolate biosynthesis pathway. CYP83A1 mainly metabolizes the aliphatic oximes to form aliphatic glucosinolate and CYP83B1 mostly catalyzes aromatic oximes to synthesis corresponding substrates for aromatic and indolic glucosinolates. In this study, two CYP83A1 genes named BcCYP83A1-1 (JQ289997), BcCYP83A1-2 (JQ289996) respectively and one CYP83B1 (BcCYP83B1, HM347235) gene were cloned from the leaves of pak choi (Brassica rapa L. ssp. chinensis var. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…In the glucosinolate biosynthesis pathway, four cytochrome P450s were found to be down-regulated at T14 compared with T7, among which CYP79B2 and the homolog CYP79B3 catalyze the conversion of tryptophan to indole-3-acetaldoxime (IAOx) (Mikkelsen et al, 2000), and CYP83A1 and CYP83B1 are oxime-metabolizing enzymes (Zhu et al, 2012). Previous studies have found correlations between resistance and a low indole GSL content (Butcher et al, 1974; Ockendon and Buczacki, 1979; Chong et al, 1985), whereas Mullin et al (1980) were not able to correlate indole GSL and resistance to clubroot.…”
Section: Discussionmentioning
confidence: 99%
“…In the glucosinolate biosynthesis pathway, four cytochrome P450s were found to be down-regulated at T14 compared with T7, among which CYP79B2 and the homolog CYP79B3 catalyze the conversion of tryptophan to indole-3-acetaldoxime (IAOx) (Mikkelsen et al, 2000), and CYP83A1 and CYP83B1 are oxime-metabolizing enzymes (Zhu et al, 2012). Previous studies have found correlations between resistance and a low indole GSL content (Butcher et al, 1974; Ockendon and Buczacki, 1979; Chong et al, 1985), whereas Mullin et al (1980) were not able to correlate indole GSL and resistance to clubroot.…”
Section: Discussionmentioning
confidence: 99%
“…In B . rapa , two CYP83A1 genes named BrCYP83A1-1 and BrCYP83A1-2 were respectively cloned from pak choi, but no functional analysis was conducted with the two genes [ 35 ]. Thiohydroximates are in turn S-glucosylated by glucosyltransferases of the UGT74 family, UGT74B1 and UGT74C1, forming desulfoglucosinolates in Arabidopsis [ 36 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…The RNA extraction and RT-PCR procedure were performed according to our previously described protocols. 23 Briefly, total RNA was extracted from samples using TRIzol reagent RNAisoTM Plus (Takara, Japan) following the manufacturer's protocols. Transcription levels were analyzed by quantitative realtime PCR (qRT-PCR), and the gene-specific primer sets were designed as described previously.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Transcription levels were analyzed by quantitative realtime PCR (qRT-PCR), and the gene-specific primer sets were designed as described previously. 23 Gene expression was normalized using Brassica actin (EX087730) as the housekeeping gene. Real-time PCR reactions were performed in triplicate on an ABI 7300 Real-Time PCR system (Applied Biosystems, Foster City, CA, USA) with the SYBR Green qPCR kit (Takara, Japan).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%